ENHANCING SELF-CONFIDENCE THROUGH PSYCHOEDUCATION AMONG STUDENTS OF SMK SULTAN ALAUDDIN, KULAI, JOHOR, MALAYSIA - Audrey Fabian; Aisyah Maharani; Daffa Rayhan Nursyahdi; Gabriela Utama Wirahmawan; Kayla Hakim Putri Kartiko; Airell Bagus Patriatama; Jovvy Sascilaputri Komala; Bellindra Dwi Zaffira Putri; Putra Ghifari Zakawali Rahim; Lintang Wahyusih Nirmala (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
This article explores the effectiveness of a psychoeducational intervention in enhancing self-confidence among students at Sekolah Menengah Kebangsaan (SMK) Sultan Alauddin Kulai, Malaysia. The study was initiated following preliminary findings that indicated low levels of self-confidence among many students, as evidenced by their pretest scores. In response, a psychoeducational program was implemented, focusing on strengthening self-concept, fostering emotional regulation, and cultivating a positive mindset. Utilizing a quantitative pretest–posttest design, the study involved a group of student participants.  The intervention began with a pretest, followed by an educational session, and concluded with a posttest using the same instrument. Pretest results showed an average score of 22.64 (56.6%), while posttest scores increased to 30.01 (75.03%), indicating a significant improvement. These findings underscore the value of school-based psychological programs in promoting students’ personal growth, particularly within the context of secondary education in Malaysia.